TEACHERS’ BELIEF ON THE IMPLEMENTATION OF ENGLISH AS A MEDIUM ISNTRUCTION (EMI) IN STEM EDUCATION (A CASE STUDY IN AN INDONESIAN CAMBRIDGE STANDARD SCHOOL) - Hindun Astiani; Rudha Widagsa (Universitas PGRI Yogyakarta, 2021)
This research aims to map out teachers‟ beliefs about, perceptions of, and classroompractices emphasizing English as the medium instruction towards STEM education. Thisstudy addresses the following research questions: (1) what are teachers‟ beliefs on applyingEnglish as the medium instruction through STEM subjects in elementary school? (2) Howdoes English as medium instruction impacts STEM subjects for elementary school? (3)What do teachers identify as challenges and barriers to use English as medium instructionin teaching STEM subjects? Moreover, this research determined as the first step to designpre-service teacher to teach STEM disciplines subjects emphasizing English as the mediuminstruction. A multi-case case study was conducted with two elementary school teachers.These two teachers were purposefully selected from a Cambridge Standard School torepresent science, mathematics, and as English teachers as well. Data collection consists ofdocument analysis, classroom observations, and interviews. Triangulation was used tovalidate the data. Data were analyzed using the constant comparative method. Findingsfrom the case studies are (1) teachers‟ beliefs influence their professional coursework,classroom practices, and how they perceived future education, (2) as the medium ofinstruction changes the classroom gets more interactive and students have fun in learning,(3) new vocabularies that students have not known and matched approach were two bigbarriers for teachers.